Evaluation and comparison of perceived exertion responses and blood lactate during a karate training session - DOI: 10.4025/reveducfis.v20i4.6454 - Milanez, Vinicius Flavio (2009)
The aim of this study was to evaluate and to compare the responses of perceived exertion (PE) and lactate concentration ([Lac]) during a conventional session of karate training. Eight athletes performed a training session, with the monitoring of the [Lac] and PE assessed using the Borg 6-20 (PE6-20) e CR-10 (PECR-10) scales. The mean results were [Lac] = 3.1 ± 1.3 mM, PE6-20 = 12.2 ± 2.2 and PECR-10 = 5.0 ± 2.1. All the investigated variables were significantly correlated with each other (r = 0.73 – 0.96, P < 0.05). The results suggest a moderate intensity of effort during the session of karate training. In addition, they suggest that both PE scales can be acceptably applied to assess the effort accomplished during the karate training session. However, the relationship between PE and [Lac] should be interpreted with caution, since other factors can contribute to the PE response.